Sedation with midazolam in flexible bronchoscopy - a prospective study - Rolo, R (2012)
INTRODUCTION: Sedatives have been increasingly used to improve patient comfort during flexible bronchoscopy (FOB). Due to its rapid-onset, anxiolytic and amnestic properties, midazolam is one of the most commonly used sedatives. OBJECTIVES: To evaluate the effect of sedation with midazolam, including patient tolerance, complications and its potential use on a daily routine basis. MATERIAL AND METHODS: A multi-centre, prospective, randomized, placebo-controlled study was made on 100 patients submitted to FOB in two Pulmonology Departments. Midazolam (0.05mg/kg) was administered to patients in Group 1 and saline solution (0,9% NaCl) to patients in Group 2, five minutes before the procedure. The Hospital Anxiety and Depression Scale (HADS-A) was used to determine patient anxiety level. Subjective questionnaires concerning main fears and complaints were answered before and after FOB. RESULTS: Mean age was 56.0 ± 14.1 years; 66% male. Most (65%) patients had low score (<7) in HADS-A scale with no difference between groups. No significant differences were seen between groups concerning FOB duration, procedures, lidocaine dosage and complications. Systolic blood pressure during and after FOB was significantly higher (p<0.003) in Group 2. Patients in Group 1 experienced less cough (32% vs 56%; p=0.03) and dyspnea (2% vs 34%; p<0.001) than in Group 2, while nausea (6% vs 18%; p>0.05) and pain (4% vs 12%; p>0.05) were not statistically different. Willingness to repeat the exam was reported in all patients in Group 1 and in 82% in Group 2 (p=0.003). CONCLUSION: Sedation with midazolam in FOB improved patient's comfort and decreased complaints, without significant haemodynamic changes. It should be offered to the patient on a routine basis.